Teacher talk as a lexical input for incidental vocabulary acquisition of young adolescent learners in APOLLO english training center = lời nói của giáo viên như một nguồn ngôn ngữ hỗ trợ việc học từ vựng không chủ đích cho trẻ vị thành niên tại Trung tâm anh ngữ APOLLO - Hoàng, Kim Ngọc (2020)
Since foreign teachers have increasingly become popular in Vietnamese EFL classroom, the researcher is motivated to examine whether their talks can effectively cater incidental vocabulary acquisition. This case study focuses on investigating the lexical profile of a teacher’s speeches in Apollo English Training Center to measure the opportunities he provided for student to unintentionally learning new words. The three criterion are: comprehensibility, repetitions and increasing intervals between exposures. After the process of recording and transcribing, a 20,000-word corpus is analyzed based on BNC-20 frequency lists in two online programs – VocabProfile and Range - available at Lextutor website. From the retrieved data, the study concludes that the provided corpus does not strictly satisfy the comprehension criterion and the number of words potential for incidental learning is relatively small. After the advantage and disadvantage of the researched teacher talk are uncovered, several recommendations to maximize the good impacts and minimize the undesired ones are proposed.